Concepts for a Monostatic Radar Transceiver Front-end in eWLB Package with Off-Chip Quasi-Circulator for 60 GHz - Schmidbauer, Philipp; Wojnowski, Maciej; Weigel, Robert; Hagelauer, Amelie Marietta (2018 IEEE 20th Electronics Packaging Technology Conference (EPTC), 2018)

Recent Trends in Wafer-Level Package Technology - Schmidbauer, Philipp; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert; Hagelauer, Amelie Marietta (International Wireless Symposium, 2020)

Wafer Level Package Integrated Antenna Concepts for Circular Polarization - Schmidbauer, Philipp; Wojnowski, Maciej; Weigel, Robert; Hagelauer, Amelie Marietta (2018 IEEE 27th Conference on Electrical Performance of Electronic Packaging and Systems (EPEPS), 2018)
We prove design concepts for embedded wafer level ball grid array package integrated circularly polarized antennas in the 57 GHz to 64 GHz ISM band. Therefore, we propose performance requirements and evaluate the properties of four different antenna-in-package layouts based on electromagnetic full-wave simulations with focus on the axial ratio characteristic
Keywords: ball grid arrays; electromagnetic wave polarisation; millimetre wave antennas; wafer level packaging; antenna-in-package layouts; ISM band; electromagnetic full-wave simulations; axial ratio characteristics; circularly polarized antennas; embedded wafer level ball grid array package; design concepts; circular polarization; wafer level package integrated antenna concepts; frequency 57 GHz to 64 GHz; Patch antennas; Bandwidth; Polarization; Antenna feeds; Layout; antenna-in-package; mm-wave packaging; heterogeneous integration